Programming and interfacing Atmel AVR microcontrollers - Grace, Thomas (Boston, MA Cengage Learning PTR, 2016)
Atmel's AVR microcontrollers are the go-to chip for many hobbyists and hardware hacking projects. In this book, Programming and interfacing Atmel AVR microcontrollers , you will learn how to program and interface using three of Atmel's microcontrollers--the ATtiny13, the ATmega328, and the ATmega32. The book begins with the binary number system and move into programming in assembly, then C and C++. Very little prior engineering knowledge is assumed. You'll work step-by-step through sections on connecting to devices such as DC motors, servos, steppers, touch pads, GPS sensors, temperature sensors, accelerometers, and more. Get started working with Atmel's AVRs today, with Programming and interfacing Atmel AVR microcontrollers
Includes index
1
Keywords: Atmel AVR microcontroller -- Programming; Programmable controllers